Asymmetric distribution of dystrophin in developing and adult Torpedo marmorata electrocyte: evidence for its association with the acetylcholine receptor-rich membrane. - Jasmin, B J (1990)
Dystrophin has been shown to occur in Torpedo electrocyte [Chang, H. W., Bock, E. & Bonilla, E. (1989) J. Biol. Chem. 264, 20831-20834], a highly polarized syncytium that is embryologically derived from skeletal muscle and displays functionally distinct plasma membrane domains on its innervated and noninnervated faces. In the present study, we investigated the subcellular distribution of dystrophin in the adult electrocyte from Torpedo marmorata and the evolution of its distribution during embryogenesis. Immunofluorescence experiments performed on adult electrocytes with a polyclonal antibody directed against chicken dystrophin revealed that dystrophin immunoreactivity codistributed exclusively with the acetylcholine receptor along the innervated membrane. At the ultrastructural level, dystrophin immunoreactivity appears confined to the face of the subsynaptic membrane exposed to the cytoplasm. In developing electrocytes (45-mm embryo), dystrophin is already detectable at the acetylcholine receptor-rich ventral pole of the cells before the entry of the electromotor axons. Furthermore, we show that dystrophin represents a major component of purified membrane fractions rich in acetylcholine receptor. A putative role of dystrophin in the organization and stabilization of the subsynaptic membrane domain of the electrocyte is discussed.